Genetic investigation of Nordic patients with complement-mediated kidney diseases - Rydberg, Viktor; Aradottir, Sigridur Sunna; Kristoffersson, Ann-Charlotte; Svitacheva, Naila; Karpman, Diana (Frontiers in Immunology, 2023)
Complement activation in atypical hemolytic uremic syndrome (aHUS), C3 glomerulonephropathy (C3G) and immune complex-mediated membranoproliferative glomerulonephritis (IC-MPGN) may be associated with rare genetic variants. Here we describe gene variants in the Swedish and Norwegian populations. Patients with these diagnoses (N=141) were referred for genetic screening. Sanger or next-generation sequencing were performed to identify genetic variants in 16 genes associated with these conditions. Nonsynonymous genetic variants are described when they have a minor allele frequency of <1% or were previously reported as being disease-associated. In patients with aHUS (n=94, one also had IC-MPGN) 68 different genetic variants or deletions were identified in 61 patients, of which 18 were novel. Thirty patients had more than one genetic variant. In patients with C3G (n=40) 30 genetic variants, deletions or duplications were identified in 17 patients, of which 9 were novel. Eight patients had more than one variant. In patients with IC-MPGN (n=7) five genetic variants were identified in five patients. Factor H variants were the most frequent in aHUS and C3 variants in C3G. Eighteen variants occurred in more than one condition.Genetic screening of patients with aHUS, C3G and IC-MPGN is of paramount importance for diagnostics and treatment. In this study we describe genetic assessment of Nordic patients in which 26 novel variants were found.